Effect of Environmental Accounting on the Quality of Accounting Disclosures of Shipping Firms in Nigeria: Array - Fakoya, Michael Bamidele; Lawal, Akeem Babatunde (The Journal of Accounting and Management, 2020)
We examine the effect of environmental accounting on the quality of accounting disclosure of shipping firms in Nigeria. Accounting reports among shipping firms are found to be deficient over time because they lack the necessary information to enable stakeholders to make informed decisions. We administered questionnaires to the staff of registered shipping firms in Nigeria and analysed data using multiple regression. Findings show that environmental accounting influences the quality of accounting disclosure of shipping firms in Nigeria. We found a significant positive association between environmental accounting and quality of accounting disclosure of shipping firms in Nigeria. Firms need to recognise a liability in the statement of assets and liabilities once it is feasible that the economic benefit of an outflow of resources will offset present obligation. We recommended that firms need to decide by discretion which expenditure or cost should include as environmental expenses or cost. Moreover, environmental costs should be capitalised or expensed as it is considered a contentious cost item for accountants and financial analyst. Firms should consider the extent of current environmental regulations and involvement; existing legal, economic, political and scientific experiences; the complexity of the environmental problem; and existing and availability of technological experience.